Observed Behavior of Reinforced Concrete and Unreinforced Masonry Buildings in April 25, 2015 Nepal Earthquake - Shrestha, Yadin (Journal of the Institute of Engineering, 2016)
In order to investigate the effects of devastating 7.8 M Gorkha Earthquake that struck Nepal on 25 April, 2015 and its aftershocks on reinforced concrete and unreinforced masonry buildings, a small survey team was dispatched from Institute of Engineering, Thapathali Campus. From the observation it was found that the earthquake caused extensive damages on the low-strength stone masonry buildings with no seismic detailing. In contrast, most of the reinforced concrete buildings sustained minor to some non-structural damages except in some localized places where the buildings were found to be collapsed by soft storey mechanism. The localized failure of reinforced concrete buildings in Kathmandu w valley and outside may be attributed to amplifcation of waves in thick soft soil deposits, poor quality of construction, inadequate column sizes and lack of ductile detailing. Journal of the Institute of Engineering, 2015, 11(1): 177-181